Corrosion behavior of a high-entropy AlCrFeNiMn alloy in a high-temperature supercritical CO2 environment - Wanhuan Yang; Xueli Zhao; Jichun Zou; Mengyao Chen; Qi Liu; Wen Yang; Shen Li; Pengrui Qiao; Weihua Zhong (Materials & Design)
A high-entropy AlCrFeNiMn alloy (AM-HEA) was corroded in a high-temperature supercritical CO2 environment at 500 °C and 25 MPa. The AM-HEA has a duplex structure with Ni,Al-enriched α region domains surrounded by Fe,Cr-enriched B2 region domains. The B2 region experienced severe corrosion, leading to the formation of large-faceted Mn-rich oxides on the exterior and flocculent oxides in the interior. Conversely, the Ni,Mn-rich domains showed minimal corrosion. A uniform, thin Al2O3 layer developed as a subsurface layer on both structures, enhancing the corrosion resistance of the AM-HEA.